2018
DOI: 10.1007/s00285-018-1299-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of bacterial growth for the maximization of metabolite production

Abstract: Microorganisms have evolved complex strategies for controlling the distribution of available resources over cellular functions. Biotechnology aims at interfering with these strategies, so as to optimize the production of metabolites and other compounds of interest, by (re)engineering the underlying regulatory networks of the cell. The resulting reallocation of resources can be described by simple so-called selfreplicator models and the maximization of the synthesis of a product of interest formulated as a dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 63 publications
2
60
0
1
Order By: Relevance
“…In this context, natural biomass maximization was achieved through a bangsingular strategy. In [5], authors showed that the same kind of strategy is necessary in order to maximize the synthetic production of a metabolite. In line with this work, we have proposed a metabolite production scheme in a CSTR Bioreactor, with the particularity that it encompasses previously studied models in the field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, natural biomass maximization was achieved through a bangsingular strategy. In [5], authors showed that the same kind of strategy is necessary in order to maximize the synthetic production of a metabolite. In line with this work, we have proposed a metabolite production scheme in a CSTR Bioreactor, with the particularity that it encompasses previously studied models in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal product maximization problem was already analyzed for this particular case in [5] where, due to the complexity of the computations in the PMP, most of the analysis was performed through a numerical approach. To allow an analytical study, we further simplify the system by assuming there is substrate in excess and the depletion occurs slowly enough (if, for example, V V ext ).…”
Section: B Substrate Depletionmentioning
confidence: 99%
See 3 more Smart Citations